Letters received by the office of the secretary of war relating to Indian affairs (National Archives microfilm publications., 1959)
Letters relating to Indian affairs in the Southeast and West Florida with letters from Benjamin Hawkins, William Augustus Bowles, and others on Creek Indians and other tribes.